Palaeomagnetism of the Brewer Conglomerate in central Australia, and fast movement of Gondwanaland during the Late Devonian - Chen, Z.; Li, Z. X.; Powell, C. McA.; Balme, B. E. (Geophysical Journal International, 1993)
Palaeomagnetic analysis of 11 diamond-drill cores from the Late Devonian Brewer Conglomerate in the northeastern part of the Amadeus Basin, central Australia, yields three magnetic components: a drilling-induced remanence (C1) acquired during the industrial drilling process, a mid- to Late Carboniferous syndeformational overprint (C2) acquired during the Alice Springs Orogeny, and a primary remanence (C3). C3 passes a fold test and gives a latest Devonian pole (BC) at 47.1°S, 041.0°E with A 95 = 6.4°. The revised APWP for Gondwanaland requires West Gondwanaland to drift across the South Pole during the Late Devonian with a speed of |20cm yr-1, while East Gondwanaland remained at low-latitude positions. It is suggested that fast plate movement occurred far more often during the Palaeozoic than has previously been thought.